Maritime Sector As A Barometer Of Surabaya's Second Progress In Indonesia With The Spirit Of Building Starting From The Periphery - Prasutiyon, Hadi; Sutrisno, Sutrisno; Tambun, Robert (Zona Laut : Jurnal Inovasi Sains Dan Teknologi Kelautan, 2025)
The importance of the socio-economic dimension of the utilization of marine potential in an area, with the existence of various regulations and technological developments, both regarding the technology of marine potential utilization tools and technology to develop and preserve the Marine potential itself, so that it can be utilized as much as possible for Prosperity. Contribution to fill the gap with socio-economic assessment of the utilization of the maritime sector of Surabaya city can be done by several steps, namely creating a” framework " for the maritime economy, then collecting and classifying socio-economic indicators that are comparable to be reliable in the maritime world. The Data obtained will allow us to assess the size of the maritime sector of the city of Surabaya and its position in the maritime claster framework made by both the provincial and central governments, as well as discuss the suitability of the strategy to form a claster at the National vs. transnational level. The results show the difference between Central and local government policies, at least at the level of implementation, expanding knowledge about marine potential that will allow to design strategies that address the real issues of marine potential utilization policies so that they become effective.